Pengaruh Lingkungan Belajar dan Kebiasaan Belajar Terhadap Hasil Belajar Desain Grafis Percetakan Siswa Kelas XI Multimedia di SMK Negeri Labuang Polewali Mandar - Nur Saidah S; Syamsurijal; Ruslan (Jurusan Teknik Informatika dan Komputer, 2020)
This research is a type of quantitative research that is ex post facto. The variables of this study are the learning environment (X1), study habits (X2) and learning outcomes (Y). The population is class XI Multimedia students, amounting to 38, while the determination of the sample using Krejcie and Morgan tables as many as 36 people. Data collection techniques used were questionnaire (questionnaire) and documentation. Data analysis techniques were performed using descriptive analysis techniques, multiple regression analysis techniques, and partial correlation analysis with categorization using the SPSS program.